2020
DOI: 10.1002/bjs5.50336
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and recurrence rate of sigmoid diverticulitis in patients requiring admission to hospital in Iceland from 1985 to 2014: nationwide population-based register study

Abstract: Background: Diverticulitis is the most common complication of diverticular disease, affecting 10-25 per cent of patients with diverticula. A retrospective, nationwide, population-based cohort study was performed to analyse the incidence and recurrence rate of sigmoid diverticulitis requiring hospital admission. Methods: All patients discharged from hospital in Iceland during 1985-2014 who were diagnosed with diverticular disease were included. The 2 test was used to analyse the trend of the incidence in the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The need for mandatory colonoscopy as a complementary investigation or as a definitive one needed for positive diagnosis of HD is still under debate, especially in private owned clinics where a rapid diagnosis is preferable to shorten the time needed for diagnosis and thus shortening the overall patient hospitalization. However, given that many studies show a high rate of incidental diagnosis of other pathologies, concurrent with HD, such as uncomplicated diverticula, diverticulitis with a silent development polyps and, of course, malignant tumors located above the reach of the standard rectal examination, we believe this type of clinical investigation should be mandatory in all clinics, as a mean of screening[ 97 - 105 ]. In our study, both clinics performed colonoscopy routinely for all grade II and above HD.…”
Section: Discussionmentioning
confidence: 99%
“…The need for mandatory colonoscopy as a complementary investigation or as a definitive one needed for positive diagnosis of HD is still under debate, especially in private owned clinics where a rapid diagnosis is preferable to shorten the time needed for diagnosis and thus shortening the overall patient hospitalization. However, given that many studies show a high rate of incidental diagnosis of other pathologies, concurrent with HD, such as uncomplicated diverticula, diverticulitis with a silent development polyps and, of course, malignant tumors located above the reach of the standard rectal examination, we believe this type of clinical investigation should be mandatory in all clinics, as a mean of screening[ 97 - 105 ]. In our study, both clinics performed colonoscopy routinely for all grade II and above HD.…”
Section: Discussionmentioning
confidence: 99%
“…The rational was to prevent complications. However, several studies have shown that the risk of severe complications decreases with the number of diverticulitis episodes (( 14 , 60 63 ). Consequently, international guidelines have been revised, and there is a consensus that the decision for elective resection should be individualized and not based on the number of previous episodes ( 49 , 64 ).…”
Section: Diagnosticsmentioning
confidence: 99%
“…Colonic diverticulosis is a common condition affecting up to 70% of the population in Western countries by the age of 80 ( 7 9 ). However only 4%–5% of patients will develop symptomatic disease, most commonly acute diverticulitis, and about 20% of these patients will have complicated diverticulitis ( 10 14 ). Thus, acute diverticulitis usually has an uncomplicated course, which is characterized by the absence of organ dysfunction, abscesses, fistula, or perforations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two-thirds of the episodes are uncomplicated, but a subset of patients present with complicated diverticulitis . Although uncomplicated diverticulitis does not require antibiotic treatment and rarely causes significant morbidity or mortality, it has a tendency to recur or develop into persistent painful diverticulitis . Further, some of the episodes of complicated diverticulitis (mainly abscesses) may be treated conservatively, but about one-third recur if the affected bowel part is not surgically removed …”
Section: Introductionmentioning
confidence: 99%